Problems in grammar and strategies being used by Arab students in speaking in English - Omer Salim, Ahnaish Milad (2010)
This study is carried out with the objective to determine and define the problems faced by Arab students in speaking in English. This is a qualitative study which seeks to understand why some ofArab students who have studied English for more than eight months in different levels up to intermediate level still have mistakes and errors in grammar when they speak. Moreover, it also aims to investigate the different strategies being used by participants during conducting the interviews and the speaking tests. Twenty participants ofArab students in Universiti Teknologi Malaysia were chosen for the study. They were selected based on their experience of studying English courses. The instruments used for this study were interviews and speaking tests. The used of these two instruments were meant to act as a triangulation of data collection in ensuring better validity and reliability ofthe findings. Results of the study show that Arab students make errors and mistakes in grammar when speaking in English, such as subject verb agreement, English articles, prepositions, tenses and plurality in nouns. In addition, the other results indicate that Arab students use same strategies when they speak, such as self- correction, asking for clarifications, using mother tongue and repeating sentences. It is recommended that the findings would provide useful insights to Arab learners into the mistakes made when they speak in English. In addition, the teachers teaching English to Arab speaking students should be aware of these problems from the beginning. Also, this study can be used as a platform for syllabus designer ofArab speaking world to plan and prepare English language curriculum taking into account the speaking errors and mistakes made by the speakers. This is to ensure that Arab learners can easily overcome these problems if schools adapt certain methods for teaching speaking in English according to common and specific errors made by Arab students.